Does personalized embryo transfer based on era improve the outcomes in patients with thin endometrium and Rif in Self Versus Donor Programme? - Priya Selvaraj; Kamala Selvaraj; Mahalakshmi Sivakumar; Hamini Chandrasekar; Valarmathi Srinivasan (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Aim: This study was designed to explore the influence of personalized Embryo Transfer (pET) with the guidance of endometrial receptivity array (ERA) on reproductive outcomes in patients with Recurrent Implantation Failure (RIF) and thin endometrium, and to determine its efficacy in self versus donor gamete programme.  Settings and designs: A retrospective study conducted from January 2014 until December 2019 at GG Hospital, Fertility research and women's speciality Centre, Chennai, India.  Methods and materials: 722 women who were inducted in this study were divided into four groups. Group A (n=179) comprised of patients using self-gametes and Group C (n=180) consisting of patients using donor gametes, patients under these groups underwent the ERA test. Both the groups were compared to their respective controls, Group B (n=181) and Group D (n=182).  Statistical analysis used: T-Test was performed using SPSS Software (12.0).  Results: Reproductive outcomes were observed to be statistically significant in patients who underwent ERA test (Group C) followed by pET. The PR was lesser in Group A (55.31%) than in Group C (68.33%). CPR was also higher in Group C (58.33%) than in Group A (48.6%). Hence, it is strongly recommended to perform pET based on ERA test for patients with thin endometrium and RIF by adjusting the progesterone exposure as per the need.  Conclusion: The present study shows that ERA test has superior benefits in patients who have previously failed despite using donor gametes. It is also apparent that ERA contributes a greater part by strengthening the reproductive outcomes in the donor gamete recipients.